The pioneers : [large type] the heroic story of the settlers who brought the American ideal west - McCullough, David G. (Thorndike Press large print popular and narrative nonfiction, 2019)
As part of the Treaty of Paris, in which Great Britain recognized the new United States of America, Britain ceded the land that comprised the immense Northwest Territory, a wilderness empire northwest of the Ohio River containing the future states of Ohio, Indiana, Illinois, Michigan, and Wisconsin. A Massachusetts minister named Manasseh Cutler was instrumental in opening this vast territory to veterans of the Revolutionary War and their families for settlement. Included in the Northwest Ordinance were three remarkable conditions: freedom of religion, free universal education, and most importantly, the prohibition of slavery. In 1788 the first band of pioneers set out from New England for the Northwest Territory under the leadership of Revolutionary War veteran General Rufus Putnam. They settled in what is now Marietta on the banks of the Ohio River. McCullough tells the story through five major characters: Cutler and Putnam; Cutler's son Ephraim; and two other men, one a carpenter turned architect, and the other a physician who became a prominent figure in American science. They and their families created a town in a primeval wilderness, while coping with such frontier realities as trees of a size never imagined, floods, fires, wolves, bears, even an earthquake, all the while negotiating a contentious and sometimes hostile relationship with the native people. Drawn in great part from a rare and all-but-unknown collection of diaries and letters by the key figures.